THE FUTURES OF SOCIAL MEDIA IN B2C MARKETING : From Business to Customers/Clients to Business to Community - Vu, Le (My University, 2020)
The thesis is a continuation of my research on social media marketing, since I already wrote a thesis in this topic over 10 years ago. Social media, as a marketing channel, has become a staple part of the business world. B2C stands for Business to Customers/Clients but it also presents Business to Community. It is the purpose of this paper to examine possible changes and movement in social media B2C marketing, and from there develop images of possible futures of this phenomenon in the next 20 years. Aside from studying the interaction between business and customers/community, risks and unexpected events are also discussed and taken into account. The assumption of this thesis is that, there will be changes and prominent movements within the two-decade timeframe. There is also an assumption that current trends (for example the emerging of social media marketing and the risk of data leaking in social media platforms) would continue and produce alternative outcomes. They would not magically disappear or easily be solved, and there would be a long progress from the present into different possible futures. In order to answer the research questions, a focus group discussion was organized. Participants varied in occupation, age, work experience and working area backgrounds. They however all had hand-on experiences with social media marketing, both from the business standpoint or customer standpoint. Data collected from the discussion was fruitful and rich. From these data, I analyzed the phenomenon dividing into different themes: social media marketing as a phenomenon, risks of social media, corporate social responsibility, or the connection between business to community, and the last one is Wild Card events. Furthermore, I used Causal Layered Analysis to develop four different images of the futures with inspiration from Jim Dator’s Four Futures. There are positive, negative, preferable futures, and also an unknown future with extraordinary Wild Card events. To conclude, the research contributes to the understandings about social media marketing, including several important elements: risks, corporate social responsibility, and possible outcomes of social media marketing in the next 20 years.
Keywords: social media, social media marketing, B2C marketing, futures studies